Evaluating the performance of educational supervisors according to total quality standards. (Journal of the College of Basic Education, 2022)
The present research aims at identifying Evaluating the performance of educational supervisors in light of the overall quality standards,Identify the quality standards for all educational supervisors from the point of view of primary school teachers,To achieve the research aim the Total quality standards tool, consisting of (34) items distributedalong fouraspects.Then, he designed a tools into three of leadership (10) items, the field of Professional growth of teachers (10) items, Class performance (8) items, Curriculum Evaluation(6) items to a sample of (500) primary school teachersout of thetotal population(7933) by (6%). To analyse the data The research used)SPSS(.The research arrived the following Conclusion:There is Total quality standards of a medium Educational supervisors in the province of Baghdad / Education Rasafa third (Sadr City).In light of the results of the research the researcher recommends some recommendation ,Engaging educational supervisors in courses to introduce them to the standards concepts and applications of comprehensive quality , In light of the results of the research and as a complement to it , the research suggests conducting a similar study for the current study on the middle and high school supervisors.